Journalistic Socialization or the Principles of Objectivity Belief Production - Schleifer, Pablo (2017)
This article considers that the social function of journalism is based on the belief in the journalistic objectivity, true illusio which involves a set of explicit and implicit rules that structure and define this social game. For this reason, we propose to investigate the processes of socialization and subjectivation that imply the incorporation of the belief in the journalistic objectivity and a series of mechanisms intended for production. In this sense, and since we postulate the need to reinstate the agent of the practices, in theoreticalmethodological link the perspective of relational sociology with the journalistic experiences reconstructed on the basis of the experiences of the journalists interviewed in our research.